Physics history e-module based on project-based learning integrated with Google Sites: Validity and practicality analysis - Rahman, Mardia Hi; Hamid, Fatma; Viyanti, Viyanti; Isra, Hutri Handayani; Irsan, Adina; Paningfat, Marita (Indonesian Journal of Science and Mathematics Education, 2025)
Innovation in learning material presentation is crucial for enhancing student engagement. This research aims to develop a physics history e-module based on the Project-based Learning (PjBL) model integrated with Google Sites and to analyze its validity and practicality as a learning resource. The research followed the ADDIE model. Validation was conducted through expert review, while a limited trial involving students assessed its practicality. Revisions were made based on evaluation results to refine the module. The findings indicated that the developed e-module was highly feasible, with a validity score of 92% and a positive student response rate of 85%. The study concludes that the e-module effectively enhances students’ understanding of physics history and can be integrated into modern learning to foster engagement. This research implies the development of Google Sites-based PjBL e-modules to improve student engagement and understanding.